2005
DOI: 10.1385/bter:105:1-3:197
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass Toxicity Associated with Inhalation Exposure to Toluene

Abstract: The inhalation of a wide range of organic solvents has become popular among young adults. Toluene is one of the most commonly used solvents in industry; it is easily available and convenient to use. Many toxicologic effects on biological systems secondary to deliberate inhalation of toluene have been reported, but investigations on adverse effects associated with bone morbidity is limited. The purpose of this study is to determine bone mineralization and investigate the adverse effects of toluene on bone. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Meanwhile, the genus Tolumonas (Fig. ), which clustered in postmenopausal women, had a negative correlation with BMD, which might be because Tolumonas is a toluene‐producing bacterium, and toluene can reduce bone density in mice and adversely affect bones . As mentioned above, alteration in the gut microbiome can result in some autoimmune and endocrine diseases; thus, some syndromes in postmenopausal women might be ameliorated by amending the function and composition of the gut microbiota.…”
Section: Resultsmentioning
confidence: 93%
“…Meanwhile, the genus Tolumonas (Fig. ), which clustered in postmenopausal women, had a negative correlation with BMD, which might be because Tolumonas is a toluene‐producing bacterium, and toluene can reduce bone density in mice and adversely affect bones . As mentioned above, alteration in the gut microbiome can result in some autoimmune and endocrine diseases; thus, some syndromes in postmenopausal women might be ameliorated by amending the function and composition of the gut microbiota.…”
Section: Resultsmentioning
confidence: 93%
“…However, no other human studies on the effects of adolescent inhalant abuse on skeletal growth could be found. Male adolescent mice exposed to toluene have significantly reduced bone mineral density compared to controls, although subsequent studies using rats did not find a reduction in bone density or skeletal microstructure following toluene exposure, rather that the bones were simply smaller …”
Section: Effects Of Inhalants On Bonementioning
confidence: 94%
“…**p≤0.01. Indeed chronic toluene exposure impairs both skeletal growth and bone mineral density in rats 16,34 and bone mineral density in adolescent males with a history of chronic glue sniffing. A break in the y axis below the 10th percentile is utilised to clearly display left-skewed data.…”
Section: Figure 1: Petrol Sniffing Is Associated With Decreased (A) Hmentioning
confidence: 96%
“…As this growth spurt can be disrupted by factors such as malnutrition 33 it is likely that inhalant abuse could disrupt this intensive growth period, including skeletal growth. Indeed chronic toluene exposure impairs both skeletal growth and bone mineral density in rats 16,34 and bone mineral density in adolescent males with a history of chronic glue sniffing. 35 Any disruption to growth during adolescence has the potential to cause long-term effects on stature.…”
Section: Figure 2: Weight Percentile Difference Between Groups Presementioning
confidence: 96%